The Role of Pela Gandong Local Wisdom in Strengthening Human Capital and the Financial Performance of MSMEs in Maluku - Pieter Novry Ruddy Rehatta; Hansen Hein Rumtutuly (Yayasan Literasi Sains Indonesia, 2026)
The financial performance of SMEs in Maluku is influenced not only by financial and technical factors but also by social capital embedded in local wisdom, such as Pela Gandong, which emphasizes solidarity, trust, and mutual cooperation. This study aims to analyze the role of Pela Gandong in strengthening human capital and enhancing the financial performance of SMEs in Maluku. This research employs a quantitative explanatory approach with a population of all SMEs in Maluku, and a sample of 234 respondents selected through purposive sampling based on the criteria of operating for at least two years and understanding the values of Pela Gandong. Data were collected using structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS). The results indicate that Pela Gandong has a significant positive effect on human capital (β = 0.645; p < 0.001) and SME financial performance (β = 0.389; p < 0.001), and human capital mediates the effect of Pela Gandong on financial performance (β = 0.542; p < 0.001). The novelty of this study lies in integrating local wisdom as strategic social capital within the Social Capital Theory framework to measure its tangible economic impact on SMEs, which has been rarely examined empirically. The findings highlight the importance of leveraging local culture-based empowerment as a strategy to improve human capital, strengthen business networks, and enhance financial performance, offering new insights for local economic policies in Maluku.